2015
DOI: 10.1002/jee.20072
|View full text |Cite
|
Sign up to set email alerts
|

Aptitude and Personality Traits in Retention of Engineering Students

Abstract: Background Engineering programs have high attrition rates, and once in college, students are unlikely to migrate to engineering from other majors. Factors that influence retention must be assessed. Purpose This study investigated the relationships of aptitude and personality traits in predicting retention for persisting students, those leaving in good standing, and those leaving in poor standing. Design/Method Participants were entering first‐year students from 2007 to 2010. Aptitude was assessed by the Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 48 publications
3
47
2
2
Order By: Relevance
“…And not all students who stay in engineering have good grades. Despite finding specific effects of academic achievement in prerequisite courses, retention is also linked to persistence and motivation (Suresh, 2006) and conscientiousness (Hall, Kauffmann, Wuensch, Swart, Deurquidi, Griffin, & Duncan, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…And not all students who stay in engineering have good grades. Despite finding specific effects of academic achievement in prerequisite courses, retention is also linked to persistence and motivation (Suresh, 2006) and conscientiousness (Hall, Kauffmann, Wuensch, Swart, Deurquidi, Griffin, & Duncan, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…[35] Also, another study found that in addition to math skills, "high [sic] school academic performance and conscientiousness were also significant predictors" of academic success in engineering. [19] Yet, in a study by Carlile 8 titled, "Predicting Performance in the Teaching Profession," the author considered the relationship between student teaching grades and the scores the student teachers made on intelligence tests, tests of teaching aptitude, grade point average in college, and Iowa State Basic Skills Exams. The author found that there was a very low relationship between the student teaching grades the students earned and intelligences tests, tests of teaching aptitude, grade point average in college, and the Iowa State Basic Skills Exams.…”
Section: Ramonmentioning
confidence: 99%
“…For example, in a metaanalysis of the relationship between motivation and academic success, 22 of 28 studies found a positive relationship 1 . Within engineering programs, both motivation 2 and conscientiousness 3 have been found to positively influence student persistence.…”
Section: Introductionmentioning
confidence: 99%